Anestesia intravenosa total com propofol ou propofol e cetamina-S(+) em araras canindé (Ara ararauna) - Jorge, Adriano Alves (2012)
The Blue and Gold Macaws (Ara ararauna) are classified as great psittacine birds and have a wide distribution in South American countries. The aim of this study was to evaluate the effects of two protocols of total intravenous anesthesia (TIVA) over the cardiovascular, respiratory systems and the recovery time, to establish safe doses and to determine whether S(+)-ketamine is effective for offsetting the side effects of propofol for anesthesia in blue and gold macaws. The analyzed parameters included included heart rate (HR), non-invasive systolic arterial pressure (SAP), respiratory frequency (ƒ), peripheral O2 saturation in hemoglobin (SpO2) , end tidal CO2 (EtCO2), cloacal temperature (CT), corneal reflex (CR) and response to inter-digital pinch (IP). All of these parameter except for CR and IP were analyzed in T0 (with the animals physically restrained). All the other parameters including CR and IP were analyzed in 5 (T5), 10 (T10), 20 (T20) and 30 (30) minutes following the induction of anesthesia. For this, eight blue and gold macaws, adults, healthy to the clinical examination, weighting 1.043±0,1 kg in the propofol group (PG) and 1.011±0,07 kg in the propofol/S(+)-ketamine group (PSKG), were submitted to intravenous (I.V.) induction with 1% propofol administered to the effect. In the PSKG, the mean propofol dose used for induction in the PG was reduced and slowly administrated, sufficiently to obtain a degree of muscle relaxation prior to the I.V. administration of S(+)-ketamine. The S(+)-ketamine was administered in a dose of 1.4 mg.kg-1 and for the administration it was previously diluted with 0.9% saline (0,06 ml of S(+)-ketamine with 1 ml of saline) to become a 0.3% S(+)-ketamine solution. For the continuous rate infusion (CRI) propofol was previously diluted in 0.9% saline (7 ml of propofol with 13 ml of saline) so that its concentration was 0.35% and so was the S(+)-ketamine diluted to reach the concentration of 0.15% (0.6 ml of S(+)-ketamine with 19.4 ml of saline). The maintenance dose in the PG was 1 mg.kg-1min1. In the PSKG, the maintenance doses were 0.15 mg.kg-1min-1 of S(+)-ketamine and 0.5 mg.kg-1min-1 of propofol, 50% less than the maintenance dose from the PG. The mean propofol induction dose (±SD) was 8.1 ± 0.89 mg.kg-1 (PG). In the PSKG, the mean doses were 4.9 ± 1.09 mg.kg-1 of propofol and 1.4 mg.kg-1 of S(+)-ketamine. The cardiovascular system was stable in both groups. In the PG, 62.5% of the macaws required ventilation support due to apnea. The EtCO2 and the SpO2values were higher in the PSKG than in the PG. In conclusion, given that the recovery times did not differ between the groups and cardiovascular stability that was provided, both protocols are safe for anesthetizing blue and gold macaws. Assisted ventilation may be required for both protocols and, S(+)-ketamine reduced the induction and maintenance doses of propofol when compared to propofol alone.